The history of the university in the language of documents (by the 100th anniversary of Dmitry Ushakov’s birth) - Серьогіна, Наталя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The compilation of documents was prepared for the 100th anniversary of the Associate Professor of V. N. Karazin Kharkiv National University, director of the Central Scientific Library of the University, hero of the Soviet Union - Dmitry Andriyovych Ushakov. A legendary man, an iconic personality who left a bright page in the 215-year history of the University. The material includes memories about Dmitry`s Andriyovych colleagues, students, friends by Astakhova Valentyna Ilarionivna, a honorary citizen of Kharkiv, Ph.D of History, a professor, Advisor to the rector of Kharkiv Humanitarian University "People’s Ukrainian Academy", by Karpov Olexandr Mykolayovych, the Candidate of Historical Sciences, professor, Ukranian People’s Deputy of the second/third/forth convocations of the Verkhovna Rada, by Ruban Valery Volodymyrovych, Associate Professor, political technologist. The paper describes the challenging life path of D. A. Ushakov, his participation in the battles at the Kursk Bulge, his commanding of the sapper unit during the forced crossing of the Dnieper River, teaching at the University and the atmosphere in the society of the era of stagnation. The memoirs tell about the conversations of Dmitry Andriyovych with colleagues about the history of the war, the events in the country, the policy of the CPSU, these conversations were absolutely frank, even critically revealing by nature. But, from the other side, holidays joyfully celebrated together, joint rest, everyday meetings with friends and colleagues were also mentioned. From pages of the memoirs all the greatness and at the same time all the modesty of this heroic person appears, it becomes clear for what colleagues respected him so much and highly appreciated the acquaintance with such an extraordinary person as Dmitry Andriyovych Ushakov. The collection also includes personal front-line letters of D. A. Ushakov to his future wife, Ella Vasyliyivna Goncharova.